2015
DOI: 10.1016/j.atherosclerosis.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

GPR40/FFA1 and neutral sphingomyelinase are involved in palmitate-boosted inflammatory response of microvascular endothelial cells to LPS

Abstract: Objectives Increased levels of both saturated fatty acids (SFAs) and lipopolysaccharide (LPS) are associated with type 2 diabetes. However, it remains largely unknown how SFAs interact with LPS to regulate inflammatory responses in microvascular endothelial cells (MIC ECs) that are critically involved in atherosclerosis as a diabetic complication. In this study, we compared the effects of LPS, palmitic acid (PA), the most abundant saturated fatty acid, or the combination of LPS and PA on interleukin (IL)-6 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…It has been also shown that GPR40 mediated thiazolidinediones‐activated proinflammatory signaling pathways . Furthermore, we have shown that GPR40 mediates palmitate‐enhanced TLR4 inflammatory signaling in vascular endothelial cells . However, a number of studies have shown that GPR40 also had anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…It has been also shown that GPR40 mediated thiazolidinediones‐activated proinflammatory signaling pathways . Furthermore, we have shown that GPR40 mediates palmitate‐enhanced TLR4 inflammatory signaling in vascular endothelial cells . However, a number of studies have shown that GPR40 also had anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous studies have shown that SFA augments LPS-induced proinflammatory gene expression in macrophages and vascular endothelial cells by amplifying TLR4-mediated inflammatory signaling such as mitogen-activated protein kinase (MAPK) and nuclear factor kappa B (NFκB) cascades. 15,25 These findings strongly suggest that free fatty acid receptors such as GPR40 and CD36 are involved in SFA-enhanced proinflammatory gene expression since SFA engages GPR40 and CD36, which mediate MAPK and NFκB signaling activation. 29,30 The role of GPR40 and CD36 in the upregulation of proinflammatory cytokine expression was further supported by our findings that inhibition of GPR40 or CD36 attenuated proinflammatory cytokine expression in gingival fibroblasts stimulated by palmitate and LPS (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Injury to the vascular endothelium can lead to dysfunction involving multiple viscera and organs, which can lead to onset and progression of heart failure (Xie et al, 2015). Endothelial barrier, composed of ECs joined through interaction of proteins, such as VE-cadherin, controls the liquid infiltrating the adjacent stroma and maintains vascular selective permeability (Lu et al, 2015). Distribution of VE-cadherin in cells can be adjusted by endocytosis, which can remove VE-cadherins from cell surface and can destroy the connection between ECs.…”
Section: Discussionmentioning
confidence: 99%